Cryopreservation of cassava (Manihot esculenta Crantz) - Adeniyi, O.J.; Akoroda, M.O.; Ng, S.Y. (2004)
This study intended to develop and/or adopt the best cryopresentation protocol for the African cassava germplasm. Eleven protocols were investigated. One protocol focused on the tolerance of pregrowth meristems to DMSO (Dimethyl sulphoxide). The other 10 were cryopresentation protocols and were employed to determine the best possible procedure involved in terms of recovery rate. Seven cultivars obtained from the International Institute of Tropical Agriculture were used. These include TMS M80/00106, TMS 63397,TMS 60142, TMS 30001, TMS 91/02324, TME 1 and TME2. Amongest the seven DMSO concentrations tested on pregrowth meristems of four genotypes, 0.5% (v/v) DMSO was the right concentration in which highest telerance was found. From the ten cryopresentation protocols carried out, five different dehydration period were tested. A 5-hr dehydration, using alginate-bead dehydration method of cryopresentation emerged the best. It was evident that modification introduced at the cryopresentation stage was reasonable as 5% DMSO performed best when used alone as a cryopretectant while 0.5% DMSO combined with calcium alginate and high sucrose proved equally good for cryopreservation of meristems and node cutting.